Effect of food on the pharmacokinetics of zoliflodacin granules for oral suspension: Phase I open‐label randomized cross‐over study in healthy subjects - Alison Luckey; Emilie Alirol; Sophie Delhomme; John O'Donnell; Esther Bettiol; John Mueller; Seamus O'Brien; Jean‐Yves Gillon (Wiley, 2023)
Abstract Gonorrhea is a sexually transmitted infection for which antibiotic treatment options have declined due to increasing antibiotic resistance. Zoliflodacin, an investigational oral spiropyrimidinetrione antibiotic with activity against Neisseria gonorrhoeae strains that are multidrug‐resistant, including to third‐generation cephalosporins, is in phase III development for uncomplicated gonorrhea. This phase I, parallel, open‐label, randomized, crossover study in healthy adults evaluated the effect of food on the pharmacokinetics of single 3 or 4 g doses of zoliflodacin administered as granules for oral suspension in the fasted state or after consumption of a standardized high‐fat meal. Forty‐seven out of 48 randomized subjects completed the study. Oral administration of zoliflodacin with food delayed the absorption rate, compared with fasted state, with time to maximum concentration (Tmax) increasing from 3 to 6 h for the 3 g dose, and 2.5 to 4 h for the 4 g dose, but had no impact on the elimination of zoliflodacin. The maximum concentration (Cmax) and area under the plasma concentration‐time curve from time 0 to 24 h (AUC(0-24)) significantly increased with food by 52% and 94% for the 3 g dose, and by 89% and 108% for the 4 g dose. Forty‐two percent of participants reported a total of 34 treatment‐emergent adverse events (TEAEs), which were all considered mild in severity. Headache was the most common TEAE (22/48 subjects, 45.8%) and the only TEAE reported in more than one subject. In conclusion, administration of single 3 and 4 g doses of zoliflodacin as granules for oral suspension, with a high‐fat meal was well‐tolerated and resulted in statistically significant increases in peak and overall systemic exposure to zoliflodacin.